Learning styles and strategies in second language classroom - Sánchez Orellana, Roxana Esmeralda (Universidad de El Salvador, 2004)
In the learning process many situations take place that can help or cause failure, in the process which will affect the successful achievement of the goals. Due to this, teachers in charge of the teaching learning process must be aware of the variety of factors that influence students’ behavior and performance in the classroom. To explain all the information related to the influence these factors have in the process, there is a brief explanation of the learning styles and learning strategies that are the main points in this research work. Taking into account the students’ differences, the multiple intelligences are recalled to demonstrate the learners’ intellectual abilities. This means that not all the students have the same capability for all the careers and they must realize their strengths and weaknesses. Grouping the multiple intelligences, the learning styles show up and they are directly related to the classroom management that is students’ real behavior in a specific learning field, in this case the English class. The visual, auditory and kinesthetic styles are defined to understand better how the students behave and do when they belong to each style. Also attitude and other aspects are considered like the ones developed early in childhood as well as the culture shock, cultural stereotypes, acculturization and social distance, and sensory information. Considering that second language learning is often second culture learning also. Referring to the sensory information it is good to mention the short term and long term memory. Short term memory is the ability of keeping information for a very brief period of time, is where conscious thinking, oral processing of information take place. It usually remains for only about 20 seconds because short-term memory is very sensitive to interruption or interference. Unless the information is important and meaningful. It is also limited in the amount of information it can hold. When overload some material drops out of short-term memory. It needs enough repeated, rehearsal or practice to recall information when needed. On the contrary the long-term memory improves while children or learners use learning strategies to store information.